Nigeria’s Border and Its Effect on the Economic and Security Development: A Case of Northern Borders in Nigeria - Mohammed, Hamza Shehu (American Finance & Banking Review, 2017)
Generally speaking, the borders in most of the African countries were among the upshot of the colonial ruling in those countries. Such demarcations were mostly created in a kind of problematic situation thereby causing serious misunderstanding among neighboring countries. It is also an imperative to know that these creations were actually perpetrated intentionally by the imperialist to serve so many purposes which includes among others the continuation of exploitation, free access to their colonies and coming back as aids providers. Moreover, such demarcations are being constructed on the papers without visiting those countries during the berlin conference in 1885 with the aid of complimenting the countries that were affected by the second world to revive them. Nevertheless, Nigeria without an exception has also faced with so many challenges in its borders especially the northern area. Therefore, this paper tries to examine why despite so many consideration by different governments and administrations yet border issues continue to be the most challenging factor in this prevailing situation in the country. Furthermore, the borders in the north were so porous to the extent that the issue of proliferation of weapons and food security were very obvious thereby challenging the security and economic wellbeing which in turn affect the nation building in the country.Based on the above, thisresearch concentrates on the qualitative technique on the area of economy and security as the drivers that highly contributed to this menaces and also measures to address it.